Inconsistencies in self-reported weather-related home damage among household members - Ha Trong Nguyen; Francis Mitrou (Global Labor Organization (GLO), 2025)
Using longitudinal, nationally representative data from Australia, this study uncovers a previously undocumented pattern: in over half of cases where one household member reports weather-related home damage, their co-resident does not. This high rate of intra-household inconsistency is striking, particularly given that respondents are asked the same question within a similar timeframe, and that prior research has generally treated self-reported damage as exogenous to individual behaviour. Household fixed-effects models indicate that a range of factors, including individual health, life satisfaction, local socio-economic conditions, and cyclone exposure, are systematically associated with both the likelihood of reporting damage and intra-household inconsistencies. Individuals in better health, with higher life satisfaction, or residing in more advantaged areas are less likely to report damage-whether consistently or inconsistently-relative to their household member. Furthermore, replacing self-reported damage with a more objective measure substantially attenuates the observed associations between damage and individual health and life satisfaction. Taken together, these findings challenge the common assumption of exogeneity in self-reported weather-related home damage and underscore the risk of biased inference if endogeneity is not adequately addressed.
Keywords: C18; Q54; R23; 330; Measurement Errors; Survey Misreporting; Natural Disasters; Cyclones; Housing